2016
DOI: 10.2105/ajph.2015.303039
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Vaccination in the United States: Uneven Uptake by Gender, Race/Ethnicity, and Sexual Orientation

Abstract: In the United States, HPV vaccine rates are lagging in men and show disparities among women. Increasing HPV vaccine uptake and series completion among women of color and all men may provide considerable long-term public health benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 6 publications
0
32
0
1
Order By: Relevance
“…With regard to our secondary outcome examining HPV vaccination, our study is one of only a few to examine differences in completion, rather than initiation, of the vaccine series by sexual orientation. The two prior studies that have investigated this outcome have yielded mixed results, with one finding no statistically significant difference in completion of the vaccine series by sexual orientation identity, 26 and the other finding a higher odds of vaccine series completion among bisexual-identified women, but a lower odds of series completion among lesbian-identified women, compared with heterosexual women. 27 Our study, which differs in methodology as it examined vaccine completion by reported sexual partners, adds to these mixed findings.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to our secondary outcome examining HPV vaccination, our study is one of only a few to examine differences in completion, rather than initiation, of the vaccine series by sexual orientation. The two prior studies that have investigated this outcome have yielded mixed results, with one finding no statistically significant difference in completion of the vaccine series by sexual orientation identity, 26 and the other finding a higher odds of vaccine series completion among bisexual-identified women, but a lower odds of series completion among lesbian-identified women, compared with heterosexual women. 27 Our study, which differs in methodology as it examined vaccine completion by reported sexual partners, adds to these mixed findings.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have identified differences in key sexual health services – including human immunodeficiency syndrome and sexually transmitted infection (HIV/STI) testing, Papanicolaou testing, and human papillomavirus (HPV) vaccination – across numerous social determinants of health. Numerous studies report differences in regard to initiation (Chao, Velicer, Slezak, & Jacobsen, 2010; Cook et al, 2010) and completion (Daniel-Ulloa, Gilbert, & Parker, 2016; Neubrand, Breitkopf, Rupp, Breitkopf, & Rosenthal, 2009; Widdice, Bernstein, Leonard, Marsolo, & Kahn, 2011) of the HPV vaccine series by race and ethnicity, where African American and Hispanic/Latina women have poorer vaccination rates than White women. National data also show that Hispanic/Latina women are least likely to have received a Pap test in the past three years (National Center for Health Statistics, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…3 However, since arriving on the market in 2006, uptake of the HPV vaccination is lower than that of other adolescent vaccines, 4 at about 30% uptake for girls and 5% for boys. 5,6 HPV vaccination provides an opportunity to reduce multiple HPV-related cancers; therefore, increasing uptake of the vaccine among youth of both sexes is a vital public health issue.…”
Section: Introductionmentioning
confidence: 99%